Non-gaussian likelihood function - Amendola, Luca (Arxiv, 1995)
We generalize the maximum likelihood method to non-Gaussian distribution functions by means of the multivariate Edgeworth expansion. We stress the potential interest of this technique in all those cosmological problems in which the determination of a non-Gaussian signature is relevant, e.g. in the analysis of large scale structure and cosmic microwave background. A first important result is that the asymptotic confidence limits on the parameters are systematically widened when the higher order correlation functions are positive, with respect to the Gaussian case.
Gesehen am 21.11.2017